The effectiveness using filter based on banana peel activated carbon for industrial wastewater treatment - Munirah Idayu , Mohd (2012)
Contamination of the river due to the wastewater discharged is becoming a serious problem nowadays, The iastewater from the industry contains pollutant such as heavy metals and organic materials. These types of contaminants are highly toxic and very dangerous to the mankind and living organism if untreated. Therefore, the wastewater need to be treated before discharging to the river. Unfortunately, the method had been used is unsatisfactory and very expensive. But, this study is a low cost treatment and very environmentally friendly by using activated carbon from banana peels waste. In this study, the filtration using banana peels activated carbon is been used to treat wastewater. Activated carbon is produced from banana peels waste to be used in the filter. Then, the test is conducted before treated and after treated,to determine the contamination in the sample. From the analysis, the percentage removal concentration of heavy metal such as lead (Pb) is highly removing about 99.23%. Other than that the percentage removal for copper, iron, zinc, and manganese is 98.75%, 98.75%, 96.44%, 93.70%, 38.71% respectively. While the percentage removal of oil and grease, COD, turbidity, TSS and BOD is 97.3%, 91.67%, 90.4%, 79.32% and 15.42% respectively. The percentage removal is due to an adsorption process occurs in the filter. From the analysis, the activated carbon from banana peels can remove heavy metal and the performance of water quality parameter increased with retention time increased. Therefore, this study has shown the effectiveness using a filter based on banana peels activated carbon for industrial wastewater treatment.